Pengenalan Identitas Budaya Nusantara Lewat Buku Mewarnai “The Time Machine Coloring Book Bernostalgia dengan Warna” - Kusumohendrarto, Raden Hadapiningrani; Fitri, Nofria Doni; Sani, Muhammad Nur (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2023)
In everyday life, a person will experience psychological ups and downs, both physically and spiritually. It can cause a person to experience fatigue, boredom, and stress. In response to this, there are many ways you can do it, one of which is by coloring an illustration book. The coloring illustration book entitled "The Time Machine Coloring Book BERNOSTALGIA dengan WARNA” presented in this book has interesting things because it contains the diverse cultural identities of the Indonesian archipelago, ranging from daily activities to objects and so on. As well as Illustrations can simultaneously provide an educational message indirectly through attractive visuals. This study will use descriptive qualitative analysis by analyzing the illustrations, text, and themes in the book. The role of this coloring book illustration is expected to be a medium for attraction, interest, education, and color therapy that introduces the cultural identity of the Indonesian archipelago, especially its traditional culture